The role of hepatic sinusoidal microenvironment in NASH: pathogenesis, animal models, and therapeutic prospects - Tan, Wanying; Deng, Jiangting; Qi, Lingjun; Tan, Zhenghuai (Frontiers in Pharmacology, 2025)
The incidence of nonalcoholic steatohepatitis (NASH) is increasing annually, posing a significant threat to human health. NASH is typified by hepatic steatosis, inflammation, and hepatocellular injury, frequently culminating in fibrosis and cirrhosis. Yet, the precise pathogenesis of NASH remains to be fully elucidated. The hepatic sinusoid, which serves as the fundamental structural and functional unit of the liver, is intricately composed of endothelial cells, Kupffer cells, and hepatic stellate cells. Consequently, the homeostasis of the hepatic sinusoidal microenvironment may exert a pivotal influence on the progression and prognosis of NASH. However, the limitations of current NASH animal models have significantly impeded advancements in understanding the disease’s pathogenesis and the development of effective therapeutic interventions. In light of these challenges, this review endeavors to delve deeper into the critical role of hepatic sinusoidal microenvironment homeostasis in the pathogenesis of NASH, critically analyze the commonly employed animal models, and comprehensively summarize the most recent and promising developments in drug research and development. It is anticipated that these efforts will collectively expedite the advancement of the field of NASH research and therapeutic innovation.